Design and development of fractal antenna for ultra high frequency band application - A. Rahim, Mohamad Kamal (Faculty of Electrical Engineering, 2008)
The Ultra High Frequency (UHF) band has long been used for voice, data and video communication. The lower frequency band of the UHF which is the 470 – 890 MHz is used for terrestrial TV broadcast. The conventional UHF antennas for receiving TV signals are quite large and directional. It would be better to have a compact and omnidirectional antenna that can be easily fabricated, especially for portable devices such as portable televisions. Koch curve fractal structure is one of the fractal geometries used in antenna designs. One of the benefits of using fractals in the design of antenna structure includes miniaturization. The dipole antenna is one of the omnidirectional that can be easily designed. The planar type of antenna is one of the easies t to fabricate. This project report describes the design of the planar fractal antenna for the uhf band using the Koch curve structure. Different shapes of antenna using the truncated ground plane have been designed and simulated to investigate which is the one that gives the best performance. The simulation process was done using the Agilent ADS software and Computer Simulation Technology CST. The antenna has been fabricated on the FR4 microstrip board with 7 . 4 = rε and thickness of 1.6 mm using the photolithography and wet etching technique. The simulation result shows that the Koch curve can be used to minimize the length of the dipole. It also shows that the folded dipole configuration together with using Koch curve can increase bandwidth and minimize the length of the antenna. The fabricated antenna have been test and measured in term of radiation pattern and return loss and it can be used at a certain band of frequencies.